The increasing inequality of wealth in China, 2002-2013 - John B. Knight; Shi Li; Haiyuan Wan (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
The inequality of wealth in China has increased rapidly in recent years. Prior to 1978 all Chinese households possessed negligible wealth. China therefore presents a fascinating case study of how inequality of household wealth increases as economic reforms take place, marketization occurs, and capital accumulates. Wealth inequality and its growth are measured and decomposed using data from two national sample surveys of the China Household Income Project (CHIP) relating to 2002 and 2013. Techniques are devised and applied to measure the sensitivity of wealth inequality to plausible assumptions about the under-representation of and the under-reporting by the wealthy. An attempt is made to explain the rising wealth inequality in terms of the relationships between income and wealth, house price inflation, differential savings, and income from wealth.
Keywords: C80; D31; P20; 330; China; wealth inequality and its decomposition; top-tail income corrections; relationships between income and wealth; house price inflation; differential savings; income from wealth